Mechanism and target treatment of primary immunodeficiency diseases with systemic lupus erythematosus‐like phenotype - Shan Liu; Zhiyong Zhang; Xuemei Tang; Xiaodong Zhao; Yunfei An (Pediatric Discovery)
Abstract Primary immunodeficiency diseases (PIDs) present a heterogeneous group of diseases with aberrant immune response caused by monogenic mutations. Due to the immune dysfunction and dysregulation, PIDs have a wide clinical spectrum such as infections, autoimmunity, autoinflammation, allergy, and malignancies. Systemic lupus erythematosus (SLE) is a systemic autoimmune disease characterized with multiple autoantibodies and multiple organ damage, which could be the predominant phenotype in patients with PIDs. In recent years, the increasing identification of monogenic causes of SLE and PIDs discloses the partially shared genetic background and common pathogenic process. The study of PIDs with SLE‐like phenotype paves the way for the exploration of lupus pathogenesis and new perspectives in targeted therapies concurrently.